Natural diet of blue swimming crab, portunus pelagicus at Strait of Tebrau, Johor, Malaysia - Ikhwanuddin, M.; Liyana, A.N.; Azra, M.N.; Bachok, Z.; Abol-Munafi, A.B. (Universiti Kebangsaan Malaysia, 2014)
Knowledge of natural diet in Portunus pelagicus is essential to understand its nutritional requirements, its interactions with other organisms and its potential for culture. The natural diet of P. pelagicus was studied in Strait of Tebrau, Johor, Malaysia via gut content analysis and molecular analysis. A total of 30 identifiable fatty acids were detected in foregut content of P. pelagicus. Fatty acid 18:3ω3 act as a mangrove detritus marker was found to be the most abundant in foregut content of both sexes of P. pelagicus and has higher value in female. PUFA was the main fatty acid found in foregut content of P. pelagicus and major contributed by fatty acid 18:3ω3, 20:5ω3 and 22:6ω3. Marine animal’s marker was found to be the dominant in foregut content of P. pelagicus and that indicated that marine animals were the main food source of P. pelagicus. In conclusion, this study showed that P. pelagicus is a primarily omnivores crab with preference of marine animal and with addition and/or incidental fed plant items.